To the question about the ways of expression of subjective modality text level (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
The article analyzes the ways of expressing of subjective modality text level, is considered subjective modality as text factor attempt to represent the process of formation of the field of subjective modality.
Keywords: subjective modality; field subjective modality text; language norm; variance; contrast; convergence